The wave : in pursuit of the rogues, freaks, and giants of the ocean - Casey, Susan, 1962- (New York : Doubleday, 2010)
Investigates colossal ship-swallowing rogue waves and the surfers who seek them out. For centuries, mariners have spun tales of gargantuan waves, 100 feet high or taller. Until recently scientists dismissed these stories; waves that high would seem to violate the laws of physics. But in the past few decades, as a number of ships have vanished and new evidence has emerged, oceanographers realized something was brewing in the planet's waters. They found their proof in February 2000, when a British research vessel was trapped in a vortex of impossibly mammoth waves in the North Sea, including several approaching 100 feet. Scientists scramble to understand this phenomenon. Yet extreme surfers fly around the world trying to ride the ocean's ultimate challenges. The sport's pioneer, Laird Hamilton, with a group of friends in Hawaii, figured out how to board waves of 70 and 80 feet. The exploits of Hamilton and his fellow surfers are juxtaposed against scientists' urgent efforts to understand the destructive powers of waves, from the tsunami that wiped out 250,000 people in the Pacific in 2004 to the 1,740 foot wave that recently leveled part of the Alaskan coast. The book portrays human beings confronting nature at its most ferocious. -- Publisher info
The grand empress -- Broken skulls -- Schrodinger's wave - - Karma, tiger sharks, and the golden carrot -- Wave good- bye -- Mavericks -- "I never saw anything like it" -- Killers -- Heavy weather -- Egypt -- Out, way out, on the Cortes bank -- The wild coast -- At the edge of the horizon
Includes bibliographical references (p. 317-324)
Keywords: Rogue waves; Surfing; Ocean waves; Oceanography